2013
DOI: 10.1002/icd.1811
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Model's Age for Young Children's Imitation: A Research Review

Abstract: The influence of a model's age on young children's behaviour has been a subject of considerable debate among developmental theorists. Despite the recent surge of interest, controversy remains about the nature of peer influence in early life. This article reviews studies that investigated the influence of a model's age on young children's behaviour in the first 5 years of life, and presents an account of seemingly mixed results. We propose that children imitate familiar behaviour for social reasons, such as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 77 publications
(89 reference statements)
3
49
0
Order By: Relevance
“…The impact on the majority bias of demonstrator age and children's cultural background also present themselves as topics worthy of future investigation: Children differentially imitate adults and similar‐aged peers (e.g. Zmyj & Seehagen, ), and children from interdependent cultures may be more inclined to copy group actions than children, like those tested here, from independent cultures (Corriveau & Harris, ).…”
Section: Discussionmentioning
confidence: 91%
“…The impact on the majority bias of demonstrator age and children's cultural background also present themselves as topics worthy of future investigation: Children differentially imitate adults and similar‐aged peers (e.g. Zmyj & Seehagen, ), and children from interdependent cultures may be more inclined to copy group actions than children, like those tested here, from independent cultures (Corriveau & Harris, ).…”
Section: Discussionmentioning
confidence: 91%
“…The awareness that adults are generally accurate when making number judgments would have led to the incorrect performance of all five of adult informants appearing highly unusual, and may have resulted in the children interpreting the incorrect responses as intentional and therefore worth adopting (McGuigan, 2012;McGuigan, Whiten, Flynn, & Horner, 2007). Indeed, the influence that unusual responses can have on children's selective copying was highlighted in a recent review that concluded that adult informants were more likely to be copied than peer informants when the response was inefficient or unusual, whereas peers were more likely to be copied when familiar actions were involved (Zmyj & Seehagen, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…For example, 2‐year‐olds are more likely to imitate novel actions from adult demonstrators (Zmyj, Daum, Prinz, & Aschersleben, ; cf. Zmyj & Seehagen, ). Three‐year‐olds prefer to learn object‐labels (Jaswal & Neely, ) and game‐rules from adults (Rakoczy, Hamann, Warneken, & Tomasello, ), are more likely to conform to an adult over a peer majority (McGuigan & Stevenson, ) and copy adults more faithfully in an over‐imitation paradigm under matched conditions (McGuigan, Makinson, & Whiten, ).…”
Section: Introductionmentioning
confidence: 99%